2012
DOI: 10.1590/s0066-782x2012005000006
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol provoca efeitos antiaterogênicos em um modelo animal de aterosclerose

Abstract: Background: Resveratrol protects the cardiovascular system by a number of mechanisms, including antioxidant and antiplatelet activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…The interactions among these cells lead to final plaque formation (3). A previous study showed that resveratrol has an overall anti-atherosclerotic effect on these various cell types in vivo (26), therefore, further investigations aim to investigate the in vitro effect of resveratrol on the interactions of these cells involved in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions among these cells lead to final plaque formation (3). A previous study showed that resveratrol has an overall anti-atherosclerotic effect on these various cell types in vivo (26), therefore, further investigations aim to investigate the in vitro effect of resveratrol on the interactions of these cells involved in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Para avaliar possíveis efeitos anti-inflamatórios e antiaterogênicos do resveratrol, um estudo utilizou modelo animal experimental com coelhos alimentados com dieta hipercolesterolêmica (1% de colesterol) concluindo que o resveratrol apresentou importantes efeitos antiaterogênicos e anti-inflamatórios (43). Outro estudo, sobre a atuação no metabolismo do colesterol e aterosclerose, evidenciou que as vias para fundamentar a cardioproteção mediada pelo resveratrol incluem a redução do estresse oxidativo e a ativação da sintetase endotelial do óxido nítrico (44).…”
Section: Compostos Fenólicos Compostos Fenólicosunclassified
“…Levando em consideração esse fato, a maioria dos estudos tem trabalhado com suplementação de resveratrol por meio de cápsulas e tabletes, pois, muitas vezes não é possível ofertar a quantidade ideal pela dieta, surgindo a necessidade de suplementação (MATOS et al, 2012;CHANG et al, 2015;LEAL et al, 2017).…”
Section: Introductionunclassified